Sportification of Esports - A systematization of sport-teams entering the esports ecosystem - Scholz, T.; Völkel, L.; Uebach, C. (International Journal of Esports, 2021)
Esports has gained much attention in recent years and mainly traditional sports clubs see esports as a way to diversify their product or brand. This is because many traditional sports are often failing to attract a young audience. Furthermore, they need to catch-up concerning digitization and internationalization. All of these aspects are substantial parts of esports. Therefore, over 400 professional sports clubs at the end of 2019 entered esports. However, there is no single strategy observable. Consequently, the goal of this paper is to systemize sports teams in esports. Based on that analysis, three cases will be presented to show the potential struggle in joining esports and why sports need to establish a strategy for entering esports. Finally, several implications for sports teams will be presented to minimize the risk of entering the esports ecosystem.